India’s Growing Strategic Capabilities and Doctrinal Shift: Implications for Strategic Stability - Hajra Sajjad (CISS Insight Journal, 2022)
Despite the overt nuclearization of South Asia in 1998, this region has remained volatile due to the on-going rivalry between India and Pakistan. After declaring itself a nuclear weapon state, having an operational doctrine is crucial for any rational state. India claims that it faces a two front war dilemma, from China in the north, and Pakistan in the west. Furthermore there is a conventional asymmetry among the regional rivals i.e. China, Pakistan and India. India therefore developed a nuclear doctrine that could counter threats from both the adversaries. Although Indian nuclear doctrine is based on the declared No First Use policy and maintaining a small nuclear arsenal for credible minimum deterrence, but the Indian threat perception has changed over time. Therefore ambiguities have emerged in its official doctrine. The paper discusses the growing Indian nuclear capabilities and their impact on its doctrinal thinking. With its growing strategic capabilities, the Indian leadership is incentivised to make a doctrinal shift towards pre-emptive counterforce strategy. Additionally, political dynamics within India posit aggressive action against its rivals in the region. This paper would also discuss whether this doctrinal shift has possibly happened, and the evidence supporting this claim, and what is its impact on arms race and deterrence stability in South Asia.